Optimizing outcome reporting after robotic flexible ureteroscopy for management of renal calculi: Introducing the concept of tetrafecta - Morshed Salah (17824244) (2024)
Robotic flexible ureteroscopy (RFURS) has shown encouraging results in terms of stone free rate (SFR) and better ergonomics compared to conventional FURS. However, few studies have reported its outcomes. The goal of this study was to report our initial results of RFURS, furthermore we proposed a novel metrics for composite outcome reporting named tetrafecta. A retrospective analysis of electronic records of 100 patients treated with RFURS for renal stones between 2019 till 2023 was performed. Tetrafecta criteria included, complete stone removal after a single treatment session, without auxiliary procedures, absence of high-grade complications (GIII-V) and same-day hospital discharge. Mean patient age and stone size were 40.7 ± 9.2 and 11.7 ± 5.8 mm, respectively. Median stone volume was 916 (421–12,235) mm3. Twenty-eight patients had multiple renal stones. Staghorn stones were seen in 12 patients. Preoperative DJ stent was fixed in 58 patients. Median operative time and stone treatment time were 116 min (97–148) and 37 (22–69) min. The median stone treatment efficiency (STE) was 21.6 (8.9–41.6). A strong positive correlation between stone volume and STE (R = 0.8, p < 0.0001). Overall, 73 patients were stone free after the initial treatment session while tetrafecta was achieved in 70 patients. Univariate analysis showed that the stone size (p = 0.008), acute infundibulopelvic angle (p = 0.023) and preoperative stenting (p = 0.017) had significant influence on achieving tetrafecta. Multivariate analysis identified preoperative stenting (OR 0.3, 95% CI 0.1–0.8, p = 0.019) as the only independent predictor of tetrafecta achievement. A comprehensive reporting methodology for reporting outcomes of RFURS is indicated for patient counseling and comparing different techniques. Tetrafecta was achieved in 70% of cases. Presence of significant residual stones ≥ 3mm was the leading cause of missing tetrafecta. Absence of preoperative stent was the only predictor of missing tetrafecta. Other Information Published in: Journal of Robotic Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11701-024-01858-1